Synthesis of Soluble Ribonucleates in Escherichia coli Infected with Bacteriophage R17 - Hudson, James B. (1968)
Measurements were made on the level of synthesis of soluble ribonucleates (sRNA) in Escherichia coli K-12 infected with the ribonucleic acid (RNA)-containing bacteriophage R17. Little or no decrease in sRNA synthesis was found to occur under conditions of infection which result in a 70 to 80% inhibition of ribosomal RNA synthesis.